Using Informational and Communicational Technologies when Training State Authority Specialists within Cooperation with European Partners (Journal of Information Technologies in Education (ITE), 2008)
In the article basic problem questions and tasks on the use of information-communication technologies in public authority’s activity and at preparation of government employee are expounded. A sequence on introduction of information-communication technologies in administrative activity and examples of computer literacy acquirement in accordance with the ECDL standards within the framework of collaboration with the European partners is resulted.